Telosticta iban sp. nov. from Sarawak (Odonata: Zygoptera: Platystictidae) - Dow, Rory A. (Zootaxa, 2014)
T. iban sp. nov. is described from the Lanjak Entimau Wildlife Sanctuary in Sarawak, Malaysian Borneo. Both sexes can be distinguished from all other species of Telosticta by the form of the antehumeral markings.